Tracking Advances in Precision Medicine for Osteoarthritis - Irham, Lalu Muhammad; Philothra, Petrina Theda (Scripta Medica, 2025)
Osteoarthritis (OA) is a prevalent degenerative joint disease that significantly affects the quality of life for millions of individuals globally. As research in this area continues to grow, conducting a bibliometric study becomes essential to analyse publication trends, identify key focus areas and assess the overall impact of research on OA. This study aimed to undertake a comprehensive bibliometric analysis of the existing literature on OA, emphasising the urgency of understanding current trends and advancements in this field. Utilising databases such as SCOPUS, the number of publications, citation metrics and collaborative networks among researchers were evaluated. Findings indicate that "osteoarthritis" is the most frequently used author keyword among the 1.911 unique keywords identified in our analysis. Notably, we observed a peak in studies related to precision medicine for OA in 2023, with a total of 127 publications projected for 2024. The International Journal of Molecular Sciences emerged as the most productive journal in this domain, publishing 17 documents specifically focused on precision medicine for OA. Furthermore, the United States was identified as the most cited country in this research area, accumulating a total of 3.953 citations. Among individual articles, The Lancet was recognised as the most cited source, with its article titled “Osteoarthritis” receiving 2.648 citations, underscoring its substantial influence on both clinical practice and further research in OA. The data also highlights that the United States leads in both single country publications (SCP) and multiple country collaborations (MCP), reflecting its extensive resources and commitment to advancing precision medicine initiatives. Given the increasing prevalence of OA and its associated healthcare burden, this bibliometric study is crucial for guiding researchers, clinicians and policymakers in developing effective interventions and improving patient outcomes. Through this analysis, we seek to promote collaboration and innovation in OA research, ultimately enhancing management strategies for this chronic condition. These collaborative efforts across various disciplines are crucial for developing effective interventions and improving outcomes for those affected by OA.